Curcumin in living biofilm: A study with confocal microscopy - Carvalho, Mariana T.; Dovigo, Lívia N. [UNESP]; Rastelli, Alessandra N.S. [UNESP]; Bagnato, Vanderlei S. (My University, 2012)
This study aimed to use confocal microscopy to evaluate different microorganisms and how photosensitizers bind to it, for this purpose we evaluate the Curcumin. We show the relation between incubation time and concentration of PS.